Antimicrobial studies on ethyl-p-methoxycinnamate and ethyl cinnamate from kaempferia galanga - Sadikun, Amirin; Ibrahim, Pazilah (1999)
Ethyl-p-methoxycinnamate and ethyl cinnamate are two major components found in the light petroleum ether extract of Kaempferia galanga. These two components together with the crude extract were tested respectively for their antimicrobial activity against eight selected organisms. Tests were performed using the agar diffusion method. Expect for Pseudomonas aeruginosa and Bacillus subtilis,the rest of the organisms were shown to be inhibited by the crude extract, ethyl-p-methoxycinnamate and ethyl cinnamate.